The Amplification of Generative Artificial Intelligence (AI) in Content Marketing For Women Micro-Entrepreneurs: Qualitative Case Study Approach - Ghonisyah, Ghaling Achmad Abdul; Asyiah, Ai Kusmiati (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: The integration of Generative Artificial Intelligence (AI) in content marketing had gained increasing attention as a key driver of digital transformation, particularly for women-led microenterprises. Purpose: This study investigates the role of generative artificial intelligence (AI) in optimizing content marketing strategies to accelerate the digitalization of female-owned microbusinesses in Indonesia. Design/methodology/approach: Using qualitative research methods, including in-depth interviews with 5 (five) participants women micro-entrepreneurs, the study emphasizes the depth of context. This study explores the challenges and benefits of adopting AI-driven content creation tools. The analytical method used is holistic coding.   Findings/results: The results reveal that Generative AI significantly enhances content production in terms of creativity, relevance, and efficiency, while also improving audience engagement and brand visibility. These findings confirm that in content creation, it is no longer necessary to pay third parties to create content, and women entrepreneurs can automatically generate the marketing content they need at no cost. Furthermore, this study highlights how AI acts as a powerful catalyst for social and economic empowerment by providing micro-businesses with the tools necessary to compete in the digital economy.  Conclusion: The research findings emphasize the transformative potential of AI in reshaping traditional marketing approaches, fostering greater inclusivity and growth in the entrepreneurial landscape. Although these entities have implemented generative AI technologies to augment the production of marketing materials, they are currently lack the specialized competency in prompt composition required to optimize the conversion potential of the resulting content for marketing purposes. Through its relevant institutions, the government is strategically promoting digital transformation by establishing dedicated digital and AI learning centers in some regions. According to the informants, however, these initiatives seldom reach female-owned micro-businesses in those same regions. Originality/value: By shedding light on the specific impact of AI on women micro-entrepreneurs, this study contributes to the broader discourse on gender, entrepreneurship, and technological innovation. The implications of this research offer valuable insights for policymakers, business practitioners, and stakeholders aiming to support the digital transformation of women-led micro-enterprises. Keywords: Generative AI, content marketing, digital skill, digital transformation, women micro-entrepreneurs